LA TEOFANÍA PROFANA EN LA OBRA POÉTICA DE VICENTE HUIDOBRO. - Pizarro Roberts, Sergio (Revista Chilena de Literatura, 2017)
Through a global and diachronic reading, this article problematizes the meaning of death in the poetry of Vicente Huidobro, establishing the gradual emergence of an eschatological subject that emits its discourse from hereafter, an unknown subject in the Chilean poetic tradition. The modification of death as a place of enunciation results in a heterodox discourse, regarding Christian beliefs, which is that of a profane theophany in whose paradoxical configuration, the figure of the palindrome is the key in order to pass this discourse of the Huidobrian speaker through the threshold of death.